Transcriptional Activation of Pyoluteorin Operon Mediated by the LysR-Type Regulator PltR Bound at a 22 bp lys Box in Pseudomonas aeruginosa M18 - Li, Sainan; Huang, Xianqing; Wang, Guohao; Xu, Yuquan (PLOS ONE, 2012)
Pseudomonas aeruginosa M18, a rhizosphere-isolated bacterial strain showing strong antifungal activity, can produce secondary metabolites such as phenazine-1-carboxylic acid and pyoluteorin (Plt). The LysR-type transcriptional regulator PltR activates the Plt biosynthesis operon pltLABCDEFG, the expression of which is induced by Plt. Here, we identified and characterized the non-conserved pltL promoter (pltLp) specifically activated by PltR and its upstream neighboring lys box from the complicated pltR–pltL intergenic sequence. The 22 bp palindromic lys box, which consists of two 9 bp complementary inverted repeats interrupted by 4 bp, was found to contain the conserved, GC-rich LysR-binding motif (T-N11-A). Evidence obtained in vivo from mutational and lacZ report analyses and in vitro from electrophoretic mobility shift assays reveals that the PltR protein directly bound to the pltLp region as the indispensable binding motif “lys box”, thereby transcriptionally activating the pltLp-driven plt operon expression. Plt, as a potential non-essential coinducer of PltR, specifically induced the pltLp expression and thus strengthened its biosynthetic plt operon expression.